Primary And Secondary Reactions Of The Fisher-Tropsh Synthesis (Eurasian Scientific Herald, 2025)
Fischer-Tropsch synthesis is a surface-catalyzed polymerization reaction. It is primarily a basic reaction that produces saturated (paraffins) and unsaturated (olefins) linear hydrocarbons (HCLCs).